2014
DOI: 10.1007/s11829-014-9322-3
|View full text |Cite
|
Sign up to set email alerts
|

Orientation behavior of predaceous ground beetle species in response to volatile emissions identified from yellow starthistle damaged by an invasive slug

Abstract: We investigated indirect defense in the yellow starthistle (Centaurea solstitialis)-grey garden slug (Deroceras reticulatum)-ground beetle (Pterostichus melanarius and Scaphinotus interruptus) system. In this host plant/ herbivore/predator system, the ground beetles are the primary predator of D. reticulatum, the dominant herbivore of the highly invasive weed, C. solstitialis. The aim of our study was to examine the behavioral responses of two species of ground beetle to olfactory stimuli emitted from yellow s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Although we know that olfactory cues can be significant in carabid detection of invertebrate prey [21, 34, 35], relatively little is known about behavioural responses of carabids to potential olfactory cues emitted by weed seeds. Better understanding differential responses of beetles to seed odours has implications for understanding weed seed predation under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although we know that olfactory cues can be significant in carabid detection of invertebrate prey [21, 34, 35], relatively little is known about behavioural responses of carabids to potential olfactory cues emitted by weed seeds. Better understanding differential responses of beetles to seed odours has implications for understanding weed seed predation under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Germacrene D was the highest overall volatile emitted when its average relative abundance is summed across all treatments. It has also been observed in high abundance in other studies of yellow starthistle (Beck et al , ; Senatore et al , ; Kilic, ; Smith and Beck, ; Oster et al , ). Germacrene D is a common plant volatile with noted semiochemical characteristics (El‐Sayed, ).…”
Section: Resultsmentioning
confidence: 55%
“…In situ flower heads of yellow starthistle were used as the target organ. Leaf volatile emissions of yellow starthistle have been well studied (Beck et al ., ; Smith and Beck, ; Oster et al ., ) with the resultant volatile profiles used to elucidate the chemical ecology of the plant and its associated biocontrol agents. Additionally, volatiles of the essential oil have been reported for aerial portions and flower heads of yellow starthistle (Senatore et al ., ; Kilic, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piesik et al (2010) observed that a 24-h exposure to leaf feeding beetles stimulated higher production of VOCs than mechanical damage of several grasses, and that both types of damage resulted in much more emission than undamaged plants. Similarly, a 24-h exposure of yellow starthistle plant leaves to slugs resulted in the detection of four sesquiterpenes from the damaged plant, whereas no volatiles were detected in the nondamaged plant (Oster et al, 2014).…”
Section: Discussionmentioning
confidence: 99%